Pain, Side Effects, and Abortion Experience Among People Seeking Abortion Care in the Second Trimester - Ilana G. Dzuba; Sruthi Chandrasekaran; Laura Fix; Kelly Blanchard; Erin King (Women's Health Reports, 2022)
Background: There is limited documentation about pain and side effects associated with dilation and evacuation (D&E) abortion, yet, pain and side effects are important factors that can affect a client's abortion experience. In 2016, Hope Clinic for Women, an independent abortion clinic in Illinois, altered its cervical preparation protocols before D&E to reduce the total time of the abortion process and improve the client experience. This analysis addresses the gap in data on client experience of abortion in the later second trimester by evaluating pain, side effects, and acceptability by gestational age. Methods: Abortion clients obtaining services at the clinic between March 2017 and June 2018 were eligible to participate if they had viable singleton pregnancies of 16?23.6 weeks' gestation, spoke English, and were at least 18 years old. Eligible participants completed a two-part survey about their abortion experience. Results: We found that respondents seeking abortion care at later gestations in the second trimester were more likely to report pain during their abortions. We did not find any association between side effects and gestational age. Conclusion: Although most respondents were prepared for the pain they experienced, some reported experiencing more pain than they expected, and more effective pain relief was commonly reported as a way to improve the service. More research on patient experiences of later abortion is needed, particularly on experiences of pain and options for pain management.